Character Education and Moral Concepts from Lichona’s and Kohlberg’s Perspectives - Azizah, Ulfa Nur (Academia Publication, 2024)
This study aimed to explore the moral concepts developed by Lichona and Kohlberg, analyzing their relevance and application within character education. Through a literature review and comparative analysis, this study examined the key principles of both Lichona’s and Kohlberg’s theories, particularly in relation to character development and moral education in educational settings. By employing a qualitative approach, the study explored how the core ideas from both theorists can be effectively integrated into character education curricula and teaching practices. The findings suggested that, while there are differences in the theoretical underpinnings of the two theories, both provided valuable insights for teaching morality in schools. The study proposed that an integrated approach, combining the strengths of both Lichona’s and Kohlberg’s frameworks, can offer a richer and more comprehensive model for fostering moral development and character education in schools.